2021
DOI: 10.3390/ijerph18105083
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alterations of Maternal Tobacco Smoking during Pregnancy: A Narrative Review

Abstract: In utero exposure to maternal tobacco smoking is the leading cause of birth complications in addition to being associated with later impairment in child’s development. Epigenetic alterations, such as DNA methylation (DNAm), miRNAs expression, and histone modifications, belong to possible underlying mechanisms linking maternal tobacco smoking during pregnancy and adverse birth outcomes and later child’s development. The aims of this review were to provide an update on (1) the main results of epidemiological stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 173 publications
(258 reference statements)
1
39
0
Order By: Relevance
“…Literature from smoked tobacco research indicates a reduction in male newborns in the presence of maternal and/or paternal cigarette smoking in a nicotine dose-dependent manner [103][104][105], and our smokers produced 43% male births, down from the worldwide average of 51.4% [106]. There is emerging evidence that changes to DNA methylation as a result of maternal smoking are greater in male offspring than female offspring [107]. However, while smoking would be expected to be associated with a decrease in birthweight, particularly in male offspring [102], we found male neonates from smokers were 500 g heavier than those from the no-tobacco group while females were on average 280 g lighter.…”
Section: Neonatal Nicotine Exposure and Outcomesmentioning
confidence: 99%
“…Literature from smoked tobacco research indicates a reduction in male newborns in the presence of maternal and/or paternal cigarette smoking in a nicotine dose-dependent manner [103][104][105], and our smokers produced 43% male births, down from the worldwide average of 51.4% [106]. There is emerging evidence that changes to DNA methylation as a result of maternal smoking are greater in male offspring than female offspring [107]. However, while smoking would be expected to be associated with a decrease in birthweight, particularly in male offspring [102], we found male neonates from smokers were 500 g heavier than those from the no-tobacco group while females were on average 280 g lighter.…”
Section: Neonatal Nicotine Exposure and Outcomesmentioning
confidence: 99%
“…The authors provide evidence that maternal smoking associated with DNA methylation changes persist during childhood. Nakamura et al [7] speculate that epigenetic mechanisms could mediate the observed associations between environmental exposures, such as maternal smoking during pregnancy, and later offspring health outcomes but further findings should strengthen this relationship. Furthermore, these effects may transfer beyond the next generation or even beyond.…”
Section: Blanc Et Al [8]mentioning
confidence: 99%
“…However, the exact mechanism leading to smoking-related diseases and deaths remains largely unknown. Recently, epigenetic regulation has become the focus of research, which can effectively explain many genomic effects that cannot be explained by protein-coding genes ( Nakamura et al, 2021 ; J. L.; Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%